Measurement of High-Power Microwave Impulse Response Characteristics of Reflector Materials - Xianggang Hu; Jiancang Su; Mingtao Zhang; Jingang Gong; Kewei Cheng; Jia Liu; Jiande Zhang; Xiaoxin Zhu; Rui Li; Jie Cheng; Shaotong Wu (International Journal of Antennas and Propagation, 2024)
High-power microwave (HPM) antenna, one of the key subsystems in the HPM system, is used for HPM radiation. Its performance is partly determined by the impulse responses of reflector materials under HPM. Therefore, it is essential to investigate the impulse response characteristics of reflector materials under HPM. Instead of the traditional waveguide cavity, this study was based on the double elliptical reflector system with an open boundary. By using this system, the impulse response of reflector materials was measured, and the response of reflector materials of multiple types under various environments with different electric field strengths and pulse widths was tested. In terms of breakdown, reflection efficiency, and pulse waveform, aluminum and carbon fiber test plates were affected by HPM and compared. Finally, the impulse response characteristics of carbon fiber test plates were summarized. The proposed method applied in this research is universal, matches the practical application environment, and can be extensively employed in the impulse response research and test of reflector materials.